The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.3109/00952999609001656
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Johnson Intervention with Four Other Methods of Referral to Outpatient Treatment

Abstract: The Johnson Intervention is a therapeutic technique in which members of the person's social network confront him or her about the damage the drinking or drug use has caused and the action they will take if treatment is refused. It is highly effective in engaging and retaining clients in inpatient treatment, but, since initial evaluations, two trends have emerged in the field. First, there has been an increase in the use of outpatient treatment and, second, a number of variations of the Johnson Intervention hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 16 publications
1
33
0
2
Order By: Relevance
“…Findings on the relationship between psychiatric status and length of stay have been inconsistent (for reviews, see Roberts andNishimoto, 1996, andStark, 1992). With respect to type of dependence, one study of a mostly male, therapeutic completion (Loneck et al, 1996(Loneck et al, , 1997. Among those who had intakes to the program studied here, employer pressure was related to a higher likelihood of returning to the program after intake to start treatment (Weisner et al, 1999).…”
Section: Need Characteristics and Treatment Retentionmentioning
confidence: 91%
“…Findings on the relationship between psychiatric status and length of stay have been inconsistent (for reviews, see Roberts andNishimoto, 1996, andStark, 1992). With respect to type of dependence, one study of a mostly male, therapeutic completion (Loneck et al, 1996(Loneck et al, , 1997. Among those who had intakes to the program studied here, employer pressure was related to a higher likelihood of returning to the program after intake to start treatment (Weisner et al, 1999).…”
Section: Need Characteristics and Treatment Retentionmentioning
confidence: 91%
“…Studies have supported the efficacy of the first approach in promoting treatment entry of the substance user (Liepman, Nirenberg, & Begin, 1989; Loneck, Garrett, & Banks, 1996a), but about 70% of the families do not actually follow through and implement the confrontation (Miller et al, 1999; Stanton, 2004). Also, one study (Loneck, Garrett, & Banks, 1996b) reported that clients who had entered treatment as the result of a confrontation were more likely to relapse than those who entered via other methods of referral.…”
Section: Introductionmentioning
confidence: 99%
“…Burke and Gregoire demonstrated that individuals in involuntary treatment were more likely to report abstinence from substance use 6 months after discharge (6). Further, individuals who are involuntarily placed into outpatient treatment programs seem to remain in treatment for just as long, or in some cases are more likely to complete the treatment, when compared with non-coerced individuals (12,13).…”
Section: Discussionmentioning
confidence: 94%